Versus: heritage for tomorrow: vernacular knowledge for sustainable architecture - Dipasquale, Letizia (2014)
This scientific publication resulted from an intensive and significant teamwork research, based on the common main aim of establishing key principles, regarding vernacular knowledge and its contribution for sustainable development. Lessons learned from vernacular heritage are systematised through principles that define a wide number of strategies to consider and to integrate for sustainable contemporary architecture. This was possible through the initial establishment of operational definitions, regarding vernacular architecture and sustainable architecture. It was also critical to define a profound reflection concerning the state of the art of environmental, socio-cultural and socio-economic sustainability, as well as resilient vernacular heritage, and the definition of parameters for vernacular sustainability during the 20th Century.